2016
DOI: 10.1634/theoncologist.2015-0303
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape of Smoldering Multiple Myeloma: A European Perspective

Abstract: Smoldering multiple myeloma (SMM) is an asymptomatic clonal plasma cell disorder and bridges monoclonal gammopathy of undetermined significance to multiple myeloma (MM), based on higher levels of circulating monoclonal immunoglobulin and bone marrow plasmocytosis without end-organ damage. Until a Spanish study reported fewer MM-related events and better overall survival among patients with high-risk SMM treated with lenalidomide and dexamethasone, prior studies had failed to show improved survival with earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…The most common indication for ASCT in Europe and the United States is MM, nevertheless elderly patients are often excluded from ASCTs, due to the patients' and/or physicians' choices, subjectivity towards its effectiveness in older cohorts, large prospective studies mostly lacking in elderly cohorts, the effectiveness and broad availability of novel agents and the fear of transplant-related toxicity. 1,2 The median age of MM patients at diagnosis is approximately 70 years, with 60% aged 65 or older and ~30% being older than 75 years. The transplant age cutoff has been proposed to be <70 years.…”
mentioning
confidence: 99%
“…The most common indication for ASCT in Europe and the United States is MM, nevertheless elderly patients are often excluded from ASCTs, due to the patients' and/or physicians' choices, subjectivity towards its effectiveness in older cohorts, large prospective studies mostly lacking in elderly cohorts, the effectiveness and broad availability of novel agents and the fear of transplant-related toxicity. 1,2 The median age of MM patients at diagnosis is approximately 70 years, with 60% aged 65 or older and ~30% being older than 75 years. The transplant age cutoff has been proposed to be <70 years.…”
mentioning
confidence: 99%
“…Therefore, the HLC assay may aid to identify high‐risk SMM patients, who should be considered for treatment initiation before CRAB criteria arise . Currently, a SFLC‐ratio >100 has been identified as a risk factor to define ultra‐high‐risk SMM or early MM, where active treatment initiation should be discussed . In analogy, our data suggest that a HLC κ/λ‐ratio of >100 or >200 may serve as a potential cut‐off, which—after future validation—may allow to identify SMM patients with earlier progression to symptomatic MM.…”
Section: Discussionmentioning
confidence: 78%
“…As depicted in Table , we also performed thorough follow‐up of the five SMM patients in order to evaluate, if HLCs could possibly serve as a risk factor for MM progression . In analogy to the SFLC‐ratio cut‐off level of >100, now defining ultra‐high‐risk SMM or active early MM, we assessed whether a defined HLC κ/λ‐ratio cutoff could help to identify SMM patients at risk to become symptomatic within ≤2 or ≤3 years: 2 of 5 of our SMM patients showed progression to symptomatic MM within 3.8 and 5.5 years, respectively. Of note, both had higher HLC IgGκ values and IgG κ/λ‐ratios compared with the remaining SMM patients (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Regarding the definition of MM-defining events, there are important studies which suggest that asymptomatic patients with more than one focal lesion detectable by magnetic resonance imaging have a higher risk of progression to symptomatic MM (>70% within 2 years). 1,[4][5][6] These patients have been described by international myeloma experts as having symptomatic disease. 5,6 Based on phase 3 studies, the bisphosphonates, pamidronate and zoledronic acid, have been found to reduce skeletal-related events compared to placebo.…”
mentioning
confidence: 99%
“…1,[4][5][6] These patients have been described by international myeloma experts as having symptomatic disease. 5,6 Based on phase 3 studies, the bisphosphonates, pamidronate and zoledronic acid, have been found to reduce skeletal-related events compared to placebo. [7][8][9] Three randomized studies have compared the effect of different bisphosphonates or different dosages of the same bisphosphonate.…”
mentioning
confidence: 99%